Characterization of Wood Cellular Structure of Plantation Grown Anogeissus leiocarpa and Eucalyptus camaldulensis in the Savannah Ecological Zone, Ghana - Enoch Gbapenuo Tampori; Francis Kofi Bih; Emmanuel Appiah-Kubi; Issah Chakurah; Michael Awotwe-Mensah; Mark Bright Donkoh (South-East European Forestry)
The decreasing availability of economic hardwood timber species throughout tropical countries has necessitated the need to adopt plantation grown exotic timber species into the mainstream of raw materials in the furniture and wood manufacturing industries. However, published research on the material properties of most of these exotic timber species grown in the Savannah Ecological Zone of Ghana is limited. The wood properties of these species when known could result in their optimal utilization and broad acceptance in the wood industries as an alternative for the extinct tropical timber species. This study determines the anatomical properties of plantation grown Anogeissus leiocarpa and Eucalyptus camaldulensis trees grown in the Savannah Ecological Zone of Ghana. Wood discs were obtained from three stem heights (butt, mid and top) from which cubes measuring 40 mm x 20 mm x 20 mm were produced for the microtome sections and macerated tissues, viewed under a microscope with Motic Image Plus software. Descriptions of wood anatomy followed IAWA's microscopic characteristics. It was observed that in the sapwood, there were more vessels than in heartwood, though the vessels were smaller in diameters, suggesting resistance to sap conduction which gives wood high aesthetic value and dimensional stability during drying. The species vessel diameter fell within the medium category and large vessels, demonstrating that wood will possess a greater mechanical strength since it will be denser, consequently possessing significant mechanical strength that can be compared favorably to other commercial timber species. This might be a major breakthrough in the production of quality and durable furniture as well as other wood products by using the exotic plantation grown timber species.